BASILIXIMAB AND ANTI-THYMOCYTE GLOBULIN AS AN INDUCTION OF IMMUNOSUPPRESSION IN RECIPIENTS OF VASCULARIZED ORGAN TRANSPLANTS - Marcin Sawczuk; Aleksandra Gradek; Dominika Nowak; Adam Zarzycki; Julia Tarnowska; Filip Szydzik; Bartosz Żegleń; Katarzyna Kozon; Monika Grudzień; Patryk Macuk (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and Aim: The advancement of immunosuppressive therapy has significantly increased organ transplantations. Among immunosuppressive agents, basiliximab and anti-thymocyte globulin (ATG) are key in induction therapy. However, clear guidelines on when to use basiliximab alone, ATG alone, or their combination are lacking, posing clinical challenges. This study aims to review recent data on basiliximab and ATG use in induction therapy post-transplant. Materials and Methods: A literature review was conducted using PubMed with keywords “basiliximab”, “ATG” and “immunosupression" including articles published up to September 2024, focusing on studies from the last two years. The review targeted information on their application in induction immunosuppression after vascularized organ transplantation, effects relative to organ type, and drug combinations. Results: Basiliximab and ATG differ in efficacy and side effects. ATG is more effective in reducing acute rejection, especially in high-risk patients, but carries higher infection and hematologic risks. Basiliximab has a better safety profile, suitable for elderly or low-risk patients. Treatment should be individualized by age, immunological risk, and infection susceptibility. Steroid continuation after basiliximab induction improves outcomes, a benefit not clearly seen with ATG. Conclusion: Induction therapy is advised for high-risk patients and certain transplants, mainly using ATG, Grafalon, or basiliximab. ATG may be a safe, effective alternative to basiliximab, which is preferred in older or comorbid patients. Limited data support ATG use in other transplants like pediatric heart transplants. Further multicenter trials and personalized therapy are needed.